The Importance of Correlation between Aldosterone and Parathyroid Hormone in Patients with Primary Hyperparathyroidism - Branka Milicic Stanic; Branislava Ilincic; Radmila Zeravica; Dragana Milicic Ivanovski; Velibor Cabarkapa; Romana Mijovic (International Journal of Endocrinology)
In primary hyperparathyroidism, an increased risk of developing the cardiovascular disease may exist due to increased activity of the renin-angiotensin-aldosterone system. The aim of this study was to evaluate the relationship between parathyroid hormone and aldosterone in patients with primary hyperparathyroidism. The study included 48 patients with primary hyperparathyroidism and 30 healthy subjects who matched age and gender to the study group. This study was conducted at the Center for Laboratory medicine, Clinical center of Vojvodina, Novi Sad, Serbia. In addition to clinical data and laboratory determination of the concentration of total and ionized calcium, phosphorus, measurements of parathyroid hormone, vitamin D, direct renin, and aldosterone were performed by the method of chemiluminescent technology. Compared to the controls, the study group had statistically significantly higher values of aldosterone (p=0.028), total calcium (p=0.01), ionized calcium (p=0.003) and parathyroid hormone (P≤0.001) Serum aldosterone and parathyroid hormone levels were correlated positively in patients with primary hyperparathyroidism (r=0.509, p<0.05). A statistically significant positive correlation between renin and parathyroid hormone (r=0.688, p<0.05) and renin and calcium (r=0.673, p<0.05) was determined in hyperparathyroid patients. In multivariate regression analysis, the strongest predictive variable of aldosterone secretion was parathyroid hormone (p=0.011). An independent relationship between parathyroid hormone and aldosterone in patients with primary hyperparathyroidism and the correlation between renin and parathyroid hormone as well as with calcium indicate not only the direct but also the indirect associations between parathyroid hormone and aldosterone in primary hyperparathyroidism. These findings may represent another possible model of renin-angiotensin-aldosterone-induced organ damage.